EFEKTIFITAS OPEN EDUCATION RESOURCES (OER) BERBASIS INQUIRY UNTUK MENINGKATKAN HOTS SISWA SMA NEGERI 2 MAGELANG - Muskitta, Marike; Arini, Ine (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: This study aims to reveal the effectiveness of inquiry-based open education resources (OER) in the form of worksheet (LKM) to improve critical thinking skills in SMAN 2 Magelang. Methods: The type of research used is a type of development research with the Research and Development (DDR) model proposed by Richey & Clein 2010. This research was carried out in March-June 2020 at the SMAN 2 Magelang. Results: The results of the calculation of the implementation of learning with the OER method showed a reliability coefficient of 0.66 so it was included in the good category. The average score on critical thinking skills is 85.7 (Very good). Conclusion: Inquiry-based OER method is effective for improving critical thinking skills of students in plant ecology courses. Keywords: OER”, thinking ability”, critical”, inquiry